Regio- and Stereoselective Palladium-Catalyzed Intermolecular Three-Component Aryletherification of Terminal Allenes - Wu, Xin-Xing; Wang, Chenjun; Zhao, Wanrong; Zhao, Haiying; Chen, Shufeng (Synthesis, 2018)
A palladium-catalyzed three-component intermolecular aryletherification reaction of ferrocene-substituted allenes, aryl iodides and phenols or alcohols is reported. In this three-component reaction, two new C–C and C–O bonds are formed in one step with high regio- and stereoselectivity. The high selectivity obtained in this reaction can be attributed to the steric effect of the bulky ferrocene group.
Keywords: aryletherification; allenes; palladium; stereoselectivity; intermolecular three-component reaction